The Average Tree Permission Value for Games with a Permission Tree - Rene van den Brink; Jean-Jacques Herings; Gerard van der Laan; Dolf Talman (Tinbergen Institute, 2012)
In the literature various models of games with restricted cooperation can be found. In those models, instead of allowing for all subsets of the set of players to form, it is assumed that the set of feasible coalitions is a proper subset of the power set of the set of players. In this paper we consider such sets of feasible coalitions that follow from a permission structure on the set of players, in which players need permission to cooperate with other players. We assume the permission structure to be an oriented tree. This means that there is one player at the top of the permission structure and for every other player there is a unique directed path from the top player to this player. We introduce a new solution for these games based on the idea of the Average Tree value for cycle-free communication graph games. We provide two axiomatizations for this new value and compare it with the conjunctive permission value.
Keywords: C71; 330; TU game; restricted cooperation; permission structure; Shapley value; Average Tree value; axiomatization; Transferable Utility Games; Shapley-Wert; Kooperatives Spiel; Theorie